The role of agriculture as an endogenous resource in local development through the example of Bátya village - Ritter, Krisztián; Áldorfainé Czabadai, Lilla; Áldorfai, György (Studia Mundi – Economica, 2017)
The role of the endogenous resources in rural development has been emphasized by the literature. During a summer research camp, the role of agriculture as an endogenous competitive factor in rural development was analyzed in a traditionally agricultural rural village Bátya (Hungary). Bátya is very famous for as an origin of a Hungarian national value (Hungarikum) - the Kalocsa pepper spice. According to our results, on one hand - in spite of the general decreasing tendency of agricultural employment - both agricultural production and the Hungarikum product still play an important role in the life of the village. On the other hand, because of the “rural exodus” and the lack of young farmers carrying on agricultural traditions, the village has started to lose its most important competitive factor.